POLITIK HUKUM PENATAAN RUANG TERBUKA HIJAU DI KOTA DUMAI DITINJAU DARI PERATURAN DAERAH KOTA DUMAI NO 15 TAHUN 2019 TENTANG RENCANA TATA RUANG WILAYAH KOTA DUMAI TAHUN 2019-2039 - Lillaha Lekterda; Dessy Artina; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Discussing legislation cannot be separated from the basic concept of therule of law in a region, besides that regional autonomy as a consequence ofimplementing the principle of decentralization has provided a lot of fresh air,especially for the regions. The regional government which is an extension of thecentral government to run the wheels of government in order to achieve the goalof being a state has the responsibility to provide the best for its people. A healthyenvironment is one that must be obtained by every citizen, especially in an urbanarea. In urban planning, green open space is one of the requirements that must bemet so that the city can carry out its functions properly and pay attention to theenvironment. There are still many cities that have not been able to meet theminimum requirements for green open space, resulting in the questioning of therole of laws in the wheels of government. This study tries to answer the existingproblems by linking legal political theory and statutory regulations in making aregulation which does not conflict with the rules above it. City spatial planning isneeded to make a city able to fulfill aspects that have been mandated by law, inthis case green open spaces as a means of supporting the life of urbancommunities who still pay attention to the environment.Keywords: Regional Regulations - Political Law - Green Open Space - SpatialPlanning